KEDUDUKAN IZIN MEMBUKA TANAH NEGARA (IMTN) DALAM PENDAFTARAN TANAH DI KOTA BALIKPAPAN - Qoriah Fadila; Wiwik Harjanti Harjanti; Aryo Subroto (Universitas Labuhanbatu, 2025)
The Permit to Open State Land (Izin Membuka Tanah Negara – IMTN) is an administrative instrument used by the Balikpapan City Government as a preliminary requirement for controlling state land prior to the formal registration of land rights. In practice, IMTN is often perceived by the public as a form of land ownership, which has led to legal ambiguity regarding the division of authority between local governments and the National Land Agency (Badan Pertanahan Nasional – BPN). This study aims to analyze the legal status of IMTN within the national land registration system and to examine its implications for legal certainty of land rights in Balikpapan City. The research employs a socio-legal approach combining normative juridical and empirical methods, through an analysis of relevant legislation and interviews with sub-district officials and the Balikpapan City Land Office. The findings indicate that IMTN does not constitute a legal basis for land ownership, but rather serves as an administrative permit functioning as preliminary evidence of physical control over state land. Consequently, IMTN cannot substitute for a land title certificate issued by BPN. The dual perception of IMTN has the potential to create legal uncertainty and overlapping authority between local governments and land administration institutions. This study recommends regulatory harmonization and strengthened institutional coordination to ensure legal certainty in land registration.Keywords: Permit to Open State Land (IMTN); Land Registration; Legal Certainty; Local Government; Balikpapan